Influence of AM–fungi and applied phosphorus on growth indices, production efficiency, phosphorus–use efficiency and fruit–succulence in okra (Abelmoschus esculentus)–pea (Pisum sativum) cropping system in an acid Alfisol - KUMAR, ANIL; CHOUDHARY, ANIL K; SURI, VINOD K (The Indian Journal of Agricultural Sciences, 2015)
The current experiment was conducted at Palampur, India during 2009–11 in okra (Abelmoschus esculentus L.)– pea (Pisum sativum L.) cropping system in RBD replicated thrice with 14 treatments comprising arbuscular mycorrhizal fungi (AMF), applied–P (50, 75 and 100% recommended P dose) and irrigation regimes (40 and 80% available water holding capacity). At active growth period (50–100 DAS), AMF imbedded treatments exhibited 7 and 20% higher absolute growth rate (AGR) in okra and pea over non–AMF counterparts, while relative growth rate (RGR) both in okra and pea was not affected significantly by AMF application. Net assimilation rate (NAR) and crop growth rate (CGR) in okra were higher by 17 and 3%, respectively with AMF inoculation, though, effect on pea was inconspicuous. At both irrigation regimes, ‘AMF + 75% soil–test based P dose’ registered statistically similar okra fruit and pea pod yields as that obtained under ‘100% soil–test based P dose’, thus, indicating an economy of about 25% soil–test based P dose. AMF inoculated plants also showed nominally higher succulence level (moisture) in okra fruits and pea pods at their picking stages compared to their non–AMF counterparts, again demonstrating a positive impact of AMF on quantitative vegetable freshness and plant water relations as well. AMF significantly enhanced the various indices of P-use efficiency in both crops. The increase in partial factor productivity (PFP), crop recovery efficiency (CRE) and % recovery (PR) of applied–P in okra under AMF inoculation was 9, 36 and 20%, respectively over non–AMF counterparts. In pea, AMF inoculation exhibited respective increase of 12, 61 and 27% in PFP, CRE and PR of applied–P over non–AMF counterparts. Production and monetary efficiencies in okra–pea cropping system were also enhanced by AMF inoculation. Overall, utilization of AMF in okra–pea cropping system indicated an economy of about 25% in soil–test based applied–P dose besides improved plant growth. AMF also revealed a tremendous potential in enhancing P- use efficiency, which otherwise is very low in acid Alfisol. Further, AMF inoculation may lead to improved fruit succulence to fetch better prices in market.